Body adiposity but not insulin resistance is associated with -675 4G/5G polymorphism in the PAI-1 gene in a sample of Mexican children - Ulises de la Cruz-Mosso; José Francisco Muñoz-Valle; Aralia Berenice Salgado-Bernabé; Natividad Castro-Alarcón; Lorenzo Salgado-Goytia; José Sánchez-Corona; Silvia Esperanza Flores-Martínez; Isela Parra-Rojas (Brazilian Society of Pediatrics, 2013)
Objective: To assess whether the -675 4G/5G polymorphism in the plasminogen activator inhibitor-1 gene is associated with obesity and insulin resistance in Mexican children. Methods: A cross-sectional study was performed in 174 children, 89 with normal-weight and 85 with obesity, aged from 6 to 13 years. All children were from state of Guerrero, and recruited from three primary schools in the city of Chilpancingo, Mexico. Insulin levels were determined by immunoenzymatic assay. The homeostasis model assessment was used to determine insulin resistance. The -675 4G/5G polymorphism in PAI-1 gene was analyzed by polymerase chain reaction-restriction fragment length polymorphism. Results: The prevalence of insulin resistance in the obese group was higher (49.41%) than in the normal-weight group (16.85%). The 4G/5G PAI-1 polymorphism was found in Hardy Weinberg equilibrium. The 4G/5G genotype contributed to a significant increase in waist-hip ratio (b = 0.02, p = 0.006), waist circumference (b = 4.42, p = 0.009), and subscapular skinfold thickness (b = 1.79, p = 0.04); however, it was not related with insulin resistance. Conclusion: The -675 4G/5G genotype of PAI-1 gene was associated with increase of body adiposity in Mexican children.